A new baby in the c-Myc-directed transcriptional machinery: Che-1/AATF. Issue 11 (3rd June 2018) - Folgiero, Valentina; Sorino, Cristina; Locatelli, Franco; Fanciulli, Maurizio
ABSTRACT: B-cell precursor acute lymphoblastic leukemia (BCP-ALL) is the most common malignancy in childhood. Despite the high cure-rate, identifying new druggable molecular targets is still of great interest. In a cohort of BCP-ALL pediatric patients, irrespectively of the molecule/karyotype lesions found, we recently observed high expression of c-Myc and Che-1/AATF, which disappears at time of remission. Study of the molecular mechanisms involved in this co-expression revealed that Che-1 expression was crucial for induction of blast-cell proliferation driven by c-Myc. Furthermore, Che-1/AATF silencing in primary BCP-ALL cell lines improves responsiveness to chemotherapy. These data individuate Che-1 as a possible novel target in the treatment of BCP-ALL able to affect c-Myc-driven tumorigenicity.